Germ Cell Tumors Ovary “Dysgerminoma” with Mayer-Rokitansky-Kuster-Hauser Syndrome - Basoeki, Rijanto Agoeng; Nabiila, Alyaa; Narulitia, Adinda; Saputra, Yoga Eko; Olfah, Trimayanti; Nursucahyo, Eko; Anas, Muhammad (Universitas Muhammadiyah Semarang, 2023)
Background: Ovarian Germ Cell Tumors originate from primitive germinal cells and can be either malignant or benign. MRKH syndrome is characterized by congenital hypoplasia of the uterus and upper vagina and can occur due to disrupted fusion of the Mullerian ducts. Diagnosis of ovarian tumors in MRKH patients is difficult but can be characterized by abdominal pain and distended.Objective: The aim of this case report is to explain the diagnostic methods and interventions performed in patients with ovarian tumors and MRKH syndrome.Case Presentation: A 25-year-old female came to the hospital with complaints of a lower abdominal lump three months ago. It was followed by severe pain, weight loss, shortness of breath, and yellowish vaginal discharge. Physical examination showed anemia, obesity, and a vagina size of 7cm with a probe. Chest X-ray showed a mass in the mediastinum and pleural effusion, and USG showed suspicion of an ovarian cyst and uterine agenesis.Conclusion: Ovarian tumor with MRKH syndrome is a rare case. Diagnosis was based on the patient’s history, clinical findings, radiologic examination, and confirmed with laparotomy and histopathology. Regular examinations are recommended to prevent and identify genital tract problems and pelvic diseases in women, especially adolescents.